Hubungan Karakteristik Perawat dengan Kepatuhan Perawat dalam Pelaksanaan SOP Pemasangan Infus - Ika Nur Aliffiyah Suudi; Dyah Wiji Puspita Sari; Retno Issroviatiningrum (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Intravenous (IV) insertion is a common nursing procedure in hospital settings, requiring strict adherence to Standard Operating Procedures (SOPs) to minimize complications such as nosocomial infections and phlebitis. However, many nurses fail to fully comply with SOPs, increasing patient safety risks. Several factors, including individual aspects such such as age, gender, educational level, and work experience are suspected to influence compliance. This study aims to examine the relationship between nurses’ characteristics and their compliance with IV insertion SOPs at Sultan Agung Islamic Hospital, Semarang. This research employed a quantitative analytical design with a cross-sectional approach. The study involved 30 nurses selected through purposive sampling. Data were obtained using a questionnaire for demographic characteristics and an observation checklist to assess SOP compliance. The data were analyzed using the Chi-Square test with a significance level of 0.05. The findings indicated that most nurses demonstrated moderate compliance (50%) or high compliance (50%), with no respondents classified as non-compliant. Statistical analysis revealed no significant relationship between age (p=0.705), gender (p=1.000), educational level (p=0.189), or years of experience (p=1.000) and IV insertion SOP compliance. These findings suggest that individual characteristics are not the primary determinants of compliance. Future research should explore other contributing factors such as hospital work environment, supervision, and patient safety culture to enhance IV insertion adherence.